The house of a thousand floors - Weiss, Jan (CEU Press classics., 2015)
A man with no memory wakes up on the deserted staircase of a gigantic building. Gradually he learns about his identity and mission: he is Petr Brok, a detective sent to rescue Tamara, the princess kidnapped by the ruler of the monstrous Mullerdom, the house of a thousand floors. Ohisver Muller is a ruthless tyrant with many faces, eyes and ears in the most remote corners of his empire. But a revolution is spreading through the floors. Yet Petr Brok soon realises that, parallel to his Mullerdom adventure, he is living another life into which he keeps drifting against his will. What is dream and.